2019
DOI: 10.1002/sdtp.13180
|View full text |Cite
|
Sign up to set email alerts
|

P‐31: Pixel Circuit with Backgate Feedback for Deep and Rich Black Expressions on Light‐Emitting Display

Abstract: A Pixel Circuit for light-emitting display is presented. The circuit improves controllability of emission current by a feedback network composed of backgate of the drive transistor. The effect is adjusted by the capacitance ratio of the topgate insulator to the backgate insulator and superimposed when the networks are connected in series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It has been reported that this problem can be solved by improving the circuit design. [1] However, in order to change the circuit design, wirings and layers are added, so that there is a concern that the circuit is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this problem can be solved by improving the circuit design. [1] However, in order to change the circuit design, wirings and layers are added, so that there is a concern that the circuit is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that the SS optimization direction of LED is different from that of OLED due to the difference in LED driving method. The high SS is desirable for OLED pixel circuits which modulate the amplitude of subthreshold current to precisely express low gray levels [26], [27], whereas the low SS is advantageous for LED pixel circuits which modulate the width of emission time for the same operation.…”
Section: Simulation and Discussionmentioning
confidence: 99%
“…the utilization of a broader data range for expressing low gray levels. Considering that conventional OLED displays tried to expand the data range for low gray levels in order to achieve deep and rich black expression [23], [24], the proposed pixel circuit is expected to offer significant advantages for the precise expression of low gray levels. Fig.…”
Section: Ccg Part Compensationmentioning
confidence: 99%